D1.1 Flexibility characterization and assessment methodologies - Wolfgang Birk; Khalid Atta (Zenodo, 2020)
The report at hand is the initial deliverable D1.1. of work package WP1 of the Flexi-Sync project which lays the foundation for the optimization strategy that will be developed to exploit the available flexibility in a district heating and cooling system. The deliverable summarizes the results from task T1.1 which is defined as follows: Task 1.1 is “Flexibility characterization”. A systematic characterization of flexibility which can be constrained from design, and can be used in control, optimization and quantification of the flexibility potential will be achieved. The characterization shall be generic in the sense that it can be applied to a large variety of components and can also consider the thermal comfort flexibility of humans residing in buildings, established as a comfort zone. Early in the project it was decided that thermal comfort flexibility of humans will not be considered in work package WP1 but instead be part of work package WP5. The deliverable contains a review of the state of the art of characterizing and assessing the flexibility in a district heating and cooling system from the perspective of operational control and optimization. A generic characterization, quantification and assessment method is described and applied to a simulated test case. The test case is the district heating system f the city Luleå in northern Sweden. The reason for using the Luleå test case is that a complete dynamic model for production, distribution and buildings, including thermal storages is available and implemented in a co-simulation environment. The results reported in D1.1 will be used with Task T1.2, T1.3, and in WP4. The work has been conducted starting in M1 and concluded in M15.